An interesting case of simultaneous bilateral Adie's tonic pupil - Saha, Indranil (Oman J Ophthalmol, 2018)
A tonic pupil is usually caused due to parasympathetic denervation of the iris sphincter muscles. It's usually seen in females and in 80 % cases it's unilateral, and 4% of these cases progress to bilateral involvement. Adie's tonic pupil has been reported in literature to have multiple syndromic associations. Simultaneous bilateral occurrence of Adie's tonic pupil in an asymptomatic healthy adult male is sparsely reported in literature. The diagnostic dilemma in the setting of a busy clinical practice is henceforth discussed.